BUILDING EFL STUDENTS’ SELF-CONFIDENCE, MOTIVATION, and ABILITY IN LISTENING ENGLISH 2.0 - Hastowohadi; Ruston Kumaini (UIBU, 2019)
The study investigates the relationship among self-confidence, motivation, and the ability of listening skill by using using 2.0. It occured when some students getting difficulty to respond listening record, they did not get any motivation while listening section is was tested to them, and practically they got less confidence to share their answer. I used mobile phone as a tool to transfer listening material, process to maintain listening class more attractive to the students. It could build up students’ self confidence, motivation, and ability in listening class. Based on the implementation of listening English 2.0, the major findings were; the students felt motivated, confidence, and built up their ability where they are correlated. They feel confidence to answer questions regarding to listening material. The students felt self confidence. These findings provide a valuable framework for lecturer/instructor in English as a Foreign Language to build up those aspects by using technology 2.0.